Kritik Hamka terhadap Institusi Adat Minangkabau melalui Novel: Kajian Analisis Strukturalisme Lévi-Strauss - Jonson Handrian Ginting (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This research is motivated by the researcher's interest in Hamka's romance novels, at least there are three novels that have some sort of the same patterns in each novel, how Hamka sees the position of Minangkabau traditional institutions in direct contact with people or outside cultures. This article tries to explore how Hamka interprets his own culture by using the Lévi-Strauss structural analysis technique through three of Hamka's novels. This study uses a descriptive qualitative research method. The data are analyzed using content–analysis technique and interactive analysis The results of this research show that Hamka is able to explain cultural phenomena and in the Minangkabau area. From the analysis, it can be seen that Hamka does not fully agree with various reactions to the Minangkabau traditional institutions, and this is also evident from his other works. Hamka also uses the novel as a tool to criticize his own culture so that the reaction in the form of resistance is not as massive as when it is conveyed openly.